2011
DOI: 10.1097/iae.0b013e31820a69ee
|View full text |Cite
|
Sign up to set email alerts
|

Central Serous Chorioretinopathy After Renal Transplantation

Abstract: Central serous chorioretinopathy develops relatively often after RT and varies in presentation and severity. The cause of CSC after RT appears to be multifactorial and closely related to corticosteroid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 44 publications
0
9
1
Order By: Relevance
“…The only population-based study found that the annual CSCR incidence per 100 000 was 5.78 in a predominantly Caucasian population 1. The prevalence of CSCR among Korean patients after renal transplantation was estimated between 1% and 6%,23 which is much higher than the 8-year period prevalence of CSCR (0.2%) in our study.…”
Section: Discussioncontrasting
confidence: 70%
“…The only population-based study found that the annual CSCR incidence per 100 000 was 5.78 in a predominantly Caucasian population 1. The prevalence of CSCR among Korean patients after renal transplantation was estimated between 1% and 6%,23 which is much higher than the 8-year period prevalence of CSCR (0.2%) in our study.…”
Section: Discussioncontrasting
confidence: 70%
“…The FA findings with clinical ophthalmic examination were classified as either classic CSC or diffuse retinal pigment epitheliopathy (DRPE). 26 Classic CSC was defined as focal or multifocal detachments of the neurosensory retina, or RPE with single or multifocal areas of leakage at late phase on FA. DRPE was defined as geographic areas of atrophy and mottling of RPE with slow, subtle leakage on FA.…”
Section: Fa and Icgamentioning
confidence: 99%
“…Patients with organ transplant are indeed subject to neurosensory macular detachment or CSC probably due to corticosteroid use. However, patients with IOTC present with serous detachment with the particularity of absence of PEDs [ 1 ]. Thus, besides the pigmentary changes, the pattern of macular detachment is distinct from idiopathic and isolated CSC after solid organ transplant.…”
Section: Case Reportmentioning
confidence: 99%
“…Although still poorly understood, it seems to be multifactorial, probably related to the use of corticosteroids and immunosuppressive agents, underlying disease and type of organ transplant received. Four distinct patterns have been described, based on fluorescein angiography (FA), including diffuse retinal pigment epitheliopathy (DRPE), focal CSC, multifocal CSC, and CSC with bullous retinal detachment (RD) [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%